2014
DOI: 10.1631/jzus.b1400010
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in apparent diffusion coefficient as an indicator of response to sorafenib in hepatocellular carcinoma

Abstract: Objective: The relationship between apparent diffusion coefficient (ADC) and chemotherapy has been established. However, whether ADC could be considered as a measure for monitoring response to sorafenib in hepatocellular carcinoma (HCC) has not been demonstrated. This study was to investigate the ADC changes of advanced HCC under sorafenib treatment. Methods: Athymic mice with HepG2 xenografts were allocated to two groups: control and sorafenib (40 mg/kg, bid). T2 and diffusion images were acquired at each tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…To our knowledge, this is the first study to obtain ADC of abdominal metastases in small animals at high magnetic field. The ADC values measured in this study are consistent with previous reports performed on primary tumors: gastric tumor ADC = 0.6-1.2x10 -3 mm 2 /s [31], intramuscular liver tumor ADC = 5-10x10 -4 mm 2 /s [37], intradermally melanoma xenograft ADC =0.53-1x10 -3 mm 2 /s [1], subcutaneous hepatocellular carcinoma ADC = 1-1.2x10 -3 mm 2 /s [8]. The hepatic metastases developed in our study had similar ADC values than brain metastases (1.3µm 2 /ms) induced by breast cancer cells [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this is the first study to obtain ADC of abdominal metastases in small animals at high magnetic field. The ADC values measured in this study are consistent with previous reports performed on primary tumors: gastric tumor ADC = 0.6-1.2x10 -3 mm 2 /s [31], intramuscular liver tumor ADC = 5-10x10 -4 mm 2 /s [37], intradermally melanoma xenograft ADC =0.53-1x10 -3 mm 2 /s [1], subcutaneous hepatocellular carcinoma ADC = 1-1.2x10 -3 mm 2 /s [8]. The hepatic metastases developed in our study had similar ADC values than brain metastases (1.3µm 2 /ms) induced by breast cancer cells [38].…”
Section: Discussionsupporting
confidence: 91%
“…Diffusion MRI allows obtaining functional information on tumors, including the physiological states (cell proliferation/density [1,2], apoptosis [3], necrosis [4]), the stages/ grades [5,6]) and responses to treatments. Indeed, diffusion MRI has been shown to be an earlier biomarker compared to tumor volume [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be due to the use of CKD‐516 as the VDA, which destroys established tumor vessels; however, the agent used in our study is an antiangiogenic drug that inhibits new vessel formation and thus may have required more time to alter tissue perfusion compared to the VDA . Our results are in good agreement with the results of several previous dynamic contrast‐enhanced MRI and basic science studies, which indicated that the tumor perfusion change after antiangiogenic drug administration should be evaluated after days or even weeks . Furthermore, similar to our results, a study monitoring the early therapeutic response to sorafenib in renal cell carcinoma xenografts using DCE‐MR revealed that the perfusion‐related metric of K trans did not exhibit any changes 24 hours after treatment .…”
Section: Discussionsupporting
confidence: 84%
“…These results strongly indicated that immune checkpoint inhibitor-based strategies will soon be primary method in the treatment of advanced HCC, and immunotherapy will introduce a new era of HCC therapy. Traditional contrast-enhanced CT and MRI, including functional imaging, are the most commonly used biomarkers for evaluating the therapeutic response in clinical practice ( 159 172 ). Research based on contrast-enhanced CT and MR images has shown the value of radiomics and DL in predicting systemic treatment efficacy for advanced HCC ( 23 , 173 175 ).…”
Section: Prediction Of the Systemic Treatment Efficacymentioning
confidence: 99%
“…Traditional contrast-enhanced CT and MRI, including functional imaging, are the most commonly used biomarkers for evaluating the therapeutic response in clinical practice(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171)(172). Research based on contrastenhanced CT and MR images has shown the value of radiomics and DL in predicting systemic treatment efficacy for advanced HCC(23,(173)(174)(175).…”
mentioning
confidence: 99%